OER provision practices in context: a socio-technical study on OpenCourseWare initiatives in Spain - Villar Onrubia, D (2014)
Based on the idea of broadening access to learning opportunities for all by means of new Information and Communication Technologies (ICTs), the Open Educational Resources (OER) movement has gained ground during the first years of the 21st Century while capturing the imagination of educators, university leaders, policy-makers and opinion leaders all over the globe. Drawing on socio-technical theories and adopting a case study research design, which involved the analysis of both qualitative and quantitative data, this thesis addresses the manifold tensions and paradoxes that may emerge out of the interplay between a highly predefined model of OER provision and the everyday realities and institutional contexts of different higher education settings. In particular, it focuses on the process of implementation by Spanish universities of OpenCourseWare (OCW) initiatives, a widely adopted model of OER provision that was originally devised at the Massachusetts Institute of Technology. By examining the enactment of technology as a situated phenomenon, this study sheds light on the roles that OCW initiatives play in relation to the strategic orientation of universities and how the actual involvement of scholars in the creation of this type of materials is often curbed by some entrenched institutional arrangements and prevailing academic cultures. The findings of this thesis have theoretical as well as practical implications, which suggest that the replication of models of OER provision outside the specific settings in which they were originally devised is a rather problematic endeavour. More generally, it supports the idea that the implementation of ICTs must be always accompanied by social structures that are mindful and respectful of local specificities and institutional arrangements. Another key conclusion is that, if universities are genuinely committed to broadening access to higher education opportunities and supporting participation in life-long learning by means of ICTs, it is crucial to understand the ways and extent to which OER initiatives can actually contribute to achieving such goals.